Application of Seeds Palm Oil Superior Based on SNI 8211:2023 for Increased Productivity - Wahono , Daryono Restu; Tampubolon , Biatna Dulbert; Prasetya , Bambang; Isharyadi , Febrian; Anggundari , Widia Citra (Research Highlights in Science and Technology Vol. 9, 2023)
The social aspect of the sustainability of palm oil has received relatively less emphasis as compared with the economic and environmental aspects. Oil palm production, especially large-scale estates, has frequently been associated with negative social impacts on rural communities, indigenous people, and estate laborers. The employment of undocumented labor and children exposes them to exploitation and violates human rights. By 2045, Indonesia hopes to produce 60 million tons of crude palm oil (CPO) annually. Approach the oil palm production and ask for the product This ongoing increase has the potential to worsen the environment. Programmes for increasing plantation palm oil production managed by commercial companies, government agencies, and smallholders have the ability to bridge the gap between the value of increasing production and the need to protect the environment. Intensification has taken place without adding new room for the associated plant [1]. Palm oil plantation utilising superior seeds for rejuvenation is the first stage of the intensification programme [2]. It is recommended that seed appropriate palm oil with Indonesian National Standard (SNI) 8211:2023, which may be used as a reference, be taken into account when conducting an intensification programme for plantation palm oil in Indonesia. In addition, the entire activity of the plantation must be certified in accordance with the standard national support policy set forth in Regulation President Number 44 of 2020 regarding the certification system for sustainable oil palm plantations in Indonesia (ISPO) [3,4]. Lack of standard procedure and documentation on the employment in oil palm plantations, particularly those involving native and indigenous groups are often associated with labor and human rights issues. SNI 8211: 2023 sets up conditions for high-quality palm oil seed production, high- quality sprouts, technical packaging terms, conditions for palm oil seed cultivation, technique cross-development, and full sale. Third stage of intensification of the national palm using SNI, where at the first stage in year planting 2014-2015 there was an improvement in production oil palm from an average of 4 tons/ha/year to 6 tons/ha/year, at stages second in 2018-2019 can increase production oil palm to 9 tons/ha/year, and at stages third in 2023-2024 breeders are hopeful that production oil palm can produce 12 tons/ha/year in the garden experiment. System intensification of planting palm oil is the right way to increase production because it can increase production of palm oil without planting area expansion. Characteristic features of the plantation palm oil system were intensive through the selection of excellent seeds, management of correct land, balanced fertilization, good irrigation, eradication of pests/disease, harvesting, and processing post-harvest. Plantation palm oil can apply technology available height for run agriculture intensive for producing more ok quality.